2018
DOI: 10.1051/bioconf/20181002026
|View full text |Cite
|
Sign up to set email alerts
|

Modelling assessment of farmers workload

Abstract: The article presents the principles of modeling the physical load assessment of farmers using Bayesian Network technology. Despite rapid development of mechanization and automation of work processes in agriculture, many farmers use their own physical strength, such as manual handling of loads. There are periods in which a farmer performs several or even a dozen of variety activities during the 24 hours. It often happens that all these activities do in a hurry, without rest, working after several hours a day, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…The study also confirmed findings of other studies that showed conventional farmers and stakeholders are very concerned about the quality of life, especially about workload [13,16,17,20]. Still, this is not surprising since overwork and physical load continue to be the greatest worry for farmers [28]. This can also be partly explained by the fact that productive, economic, and social conditions determine young people's willingness to take up farming [13].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The study also confirmed findings of other studies that showed conventional farmers and stakeholders are very concerned about the quality of life, especially about workload [13,16,17,20]. Still, this is not surprising since overwork and physical load continue to be the greatest worry for farmers [28]. This can also be partly explained by the fact that productive, economic, and social conditions determine young people's willingness to take up farming [13].…”
Section: Discussionsupporting
confidence: 87%
“…Although conventional farmers consider the environment and natural resources as important elements of their daily work, while ethical and social values are also important to them [31], they are profit-driven (i.e., the environment is justified by ethical, social, and ecological values, but requires economic sacrifices) and are willing to introduce changes and implement innovations if they expect positive economic results and/or receive full direct payments [20]. Thus, conventional farmers would consider the environment when (economic) initiatives are in place to do so [28]. Conventional farmers ranked climate change below food security, energy security, and water quality in terms of important issues facing society [30].…”
Section: Discussionmentioning
confidence: 99%